Identifying Factors Associated with High-Risk Obstructive Sleep Apnea (OSA) among Hypertensive Patients: A Case-Control Study in A Tertiary Care Hospital in Pakistan: Identifying Factors Associated with High-Risk OSA among Hypertensive Patients - Haq, Ihtisham Ul; Ikram, Hareem; Bibi, Asma; Ayub, Ayaz; Hussain, Hamid; Rahim, Tariq (Pakistan Journal of Health Sciences, 2026)
Obstructive sleep apnea (OSA) involves repeated upper-airway collapse and intermittent hypoxia. In hypertensive patients, particularly in developing regions, undetected OSA exist which significantly increases cardiovascular dangers. Objective: To identify factors associated with high-risk OSA in patients with raised blood pressure attending two tertiary hospitals in Peshawar. Methods: This case-control study (June 2025–September 2025) included 156 hypertensive adults (78 cases, 78 controls). Inclusion required a diagnosis of hypertension and a specific STOP-Bang score (cases ≥ 3; controls ≤ 2). Exclusion criteria involved prior OSA treatment, pregnancy, resistant hypertension, or severe mental health conditions. Data were collected via structured questionnaires and analyzed using multivariable logistic regression. Results: Mean age, BMI, and neck circumference were significantly higher in the high-risk group (p<0.001). Gender, BMI category, and ischemic heart disease were significantly associated. In crude regression, age, gender, BMI, neck circumference, and ischemic heart disease were significant predictors; however, after adjustment, only older age, male gender, and larger neck circumference remained independently associated with high-risk OSA. Conclusions: Older age, male gender, and increased neck circumference independently predict high-risk OSA in hypertensive patients. STOP-Bang proved useful as a screening tool, and the high prevalence of anxiety highlights the broader clinical burden. Incorporating neck circumference and age into routine hypertension care may aid earlier OSA recognition.